2023
DOI: 10.1021/acsanm.3c03016
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reduction Catalyzed by Pt Nanoparticles Confined in Mesoporous Carbon Supports Doped with Single Fe Atoms

Chen Yang,
Yadong Li,
Xilong Wang
et al.

Abstract: Enhancing the homodispersion of Pt nanoparticles and their interaction with carbon supports is a promising strategy for improving the activity and stability of Pt-based catalysts in proton-exchange membrane fuel cells. We have developed a highly efficient and durable catalyst by confining Pt nanoparticles in a mesoporous carbon support doped with single Fe atoms (named as Pt/Meso Fe1-NC). The Pt/Meso Fe1-NC catalyst, which combined the pore confinement effect with the electronic metal–support interaction strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…DFT calculations further revealed that the Fe−N−C carrier can provide strong and stable support for Pt nanoparticles and regulate the electronic structure through synergistic effects to mitigate the demetallization of Pt and Fe. Subsequently, Yang and colleagues 159 combined the pore confinement effect and EMSI strategy to develop an efficient and durable catalyst, ), power density (824 mW cm −2 at 0.67 V), and stability (overpotential loss of only 23 mV at 1.0 A cm −2 ). To further enhance the stability of the Pt 3 Co/FeN 4 catalyst, Wu's group 101 replaced the carrier Fe−N−C with low-Fenton-effect Mn−N−C, resulting in the development of a catalyst (L12-Pt 3 Co@Mn SA −NC) with ordered L12-Pt 3 Co nanoparticles (3.3 nm) uniformly dispersed on the Mn SA −NC carrier.…”
Section: Construct Single-atom-supported Metal Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…DFT calculations further revealed that the Fe−N−C carrier can provide strong and stable support for Pt nanoparticles and regulate the electronic structure through synergistic effects to mitigate the demetallization of Pt and Fe. Subsequently, Yang and colleagues 159 combined the pore confinement effect and EMSI strategy to develop an efficient and durable catalyst, ), power density (824 mW cm −2 at 0.67 V), and stability (overpotential loss of only 23 mV at 1.0 A cm −2 ). To further enhance the stability of the Pt 3 Co/FeN 4 catalyst, Wu's group 101 replaced the carrier Fe−N−C with low-Fenton-effect Mn−N−C, resulting in the development of a catalyst (L12-Pt 3 Co@Mn SA −NC) with ordered L12-Pt 3 Co nanoparticles (3.3 nm) uniformly dispersed on the Mn SA −NC carrier.…”
Section: Construct Single-atom-supported Metal Catalystsmentioning
confidence: 99%
“…DFT calculations further revealed that the Fe–N–C carrier can provide strong and stable support for Pt nanoparticles and regulate the electronic structure through synergistic effects to mitigate the demetallization of Pt and Fe. Subsequently, Yang and colleagues combined the pore confinement effect and EMSI strategy to develop an efficient and durable catalyst, confining Pt nanoparticles within mesoporous carbon doped with single iron atoms (named Pt/Meso Fe 1 –NC). Benefiting from the spatial confinement and EMSI strategy, Pt/Meso Fe 1 –NC exhibited excellent durability in acidic ORR, with an overpotential loss of only 6 mV after 30 000 cycles in 0.1 M HClO 4 .…”
Section: Application Of Single-atom-supported Metal Catalysts In Pemf...mentioning
confidence: 99%